An Examination of Telemedicine Adoption: Unpacking the Determinants of Behavioral Intention through an Extended UTAUT - Lis Lesmini; Muhammad Iqbal Firdaus; Hana Wiedya; Jessynia Rasya Vicahya (Jurnal Siber Multi Disiplin, 2026)
The COVID-19 pandemic has led to changes in people’s lives, including the increased use of telemedicine services. Extending the UTAUT framework, the purpose of this study is to analyze the factors that influence behavioral intentions towards the adoption of telemedicine platforms and investigate the role of e-trust in promoting the use of telemedicine. A non-probability sampling approach was used to select a research sample of 204 respondents. The SEM-PLS model was used in this quantitative research. The population of this study is Halodoc users. The study found that performance expectancy, effort expectancy, facilitating conditions, and e-trust all had significant, direct, and positive effects on respondents’ intentions to use telemedicine. The findings also revealed that social influence influences e-trust in online healthcare systems. No significant relationship between social influence and behavioral intention was found. The present study suggests a positive attitude toward technology can increase user intention in healthcare systems.